Coated ternary precursor based on spray pyrolysis, preparation method and battery

CN122831406APending Publication Date: 2026-09-29JINGMEN GEM NEW MATERIAL CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610926088.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

但在用于制备包覆改性的三元正极前驱体时,包覆的步骤往往需要借助其他设备得以实现,如何在喷雾热解工艺中高效实现包覆层的均匀且可控构筑,并进一步推动其向规模化,可控制备方向发展,仍是当前面临的重要挑战

Benefits of technology

[0032]由于高镍单晶正极材料在长周期充放电过程中易产生微裂纹,从而暴露出活性表面,加剧与电解液的副反应,导致界面稳定性下降与性能衰退,通过表面包覆改性构筑均匀的惰性或导离子覆盖层,可有效抑制裂纹扩展、减少界面副反应,是提升该材料结构完整性及电化学稳定性的关键策略之一。而相较于传统共沉淀法多步反应,耗时冗长(通常需数十小时)的制备流程,本发明提供的二次喷雾热解工艺将前驱体合成与表面包覆整合于连续喷雾系统中,大幅缩短制备周期至小时级别,且避免了多步骤分离、洗涤与再分散带来的批次不一致性与成本上升的问题,该技术具有突出的工艺集约性与可扩展性,能够适应动力电池产业对高一致性、高稳定性正极材料快速增产的需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention provides a spray-assisted pyrolysis-based coated ternary precursor, its preparation method, and a battery. The preparation method includes the following steps: performing a first spray pyrolysis on a nickel-cobalt-manganese mixed salt solution to obtain a core; mixing the core with a coating solution and performing a second spray pyrolysis to obtain the spray-assisted pyrolysis-based coated ternary precursor; the nickel-cobalt-manganese mixed salt solution includes a first additive, which includes a polyol; the coating solution includes a second additive, which includes a two-dimensional material. The preparation method of this invention, through a spray-assisted secondary pyrolysis process combined with specific additives, can achieve efficient and uniform construction of an atomic-scale coating layer on the surface of precursor particles, significantly improving the preparation efficiency and large-scale production capability of coated high-nickel ternary precursors, while also improving battery capacity and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology, and relates to a coated ternary precursor based on spray pyrolysis, its preparation method, and a battery. Background Technology

[0002] Lithium-ion batteries are widely used in electric vehicles due to their high energy density and long cycle life. Cathode materials account for approximately 30% to 35% of battery manufacturing costs and are a key factor influencing battery prices. Among these, ternary materials dominate due to their high energy density and superior performance. However, traditional production processes for ternary materials are cumbersome, energy-intensive, and polluting. Spray pyrolysis, which synthesizes materials in a one-step process by atomizing a precursor solution in a high-temperature flame, offers advantages such as simple process, short processing time, no liquid phase byproducts, low cost, and ease of industrial scale-up. It can produce high-performance precursor materials with low impurities and uniform particle size. Currently, spray pyrolysis technology has been applied in many fields (such as catalysts and solar cells). Further research is needed on how to achieve targeted product production in the manufacturing of ternary precursor materials by adjusting equipment parameters.

[0003] Furthermore, high-nickel cathode materials are prone to lattice cracks caused by structural stress during cycling, leading to capacity decay and performance degradation. Surface coating modification is an effective strategy to suppress the formation of such cracks. However, traditional co-precipitation coating methods have limitations such as long process cycles and cumbersome steps. In contrast, spray pyrolysis has potential advantages such as high process integration and good component uniformity. For example, CN118791054A discloses a coated precursor oxide and its preparation method and application. It first prepares oxides through spray pyrolysis technology, then coats the oxide particles in a fluidized bed, and obtains a coated oxide precursor after drying and solidification. However, when used to prepare coated modified ternary cathode precursors, the coating step often requires the use of other equipment. How to efficiently achieve uniform and controllable construction of the coating layer in the spray pyrolysis process, and further promote its development towards large-scale and controllable preparation, remains an important challenge. Summary of the Invention

[0004] The purpose of this invention is to provide a coated ternary precursor based on spray pyrolysis, a preparation method thereon, and a battery. The preparation method, through a spray-assisted secondary pyrolysis process combined with specific additives, can achieve efficient and uniform construction of an atomic-scale coating layer on the surface of precursor particles, significantly improving the preparation efficiency and large-scale production capacity of coated high-nickel ternary precursors, while also improving the battery capacity and cycle performance.

[0005] To achieve this objective, the present invention adopts the following technical solution:

[0006] In a first aspect, the present invention provides a method for preparing a coated ternary precursor based on spray pyrolysis, the method comprising the following steps:

[0007] A nickel-cobalt-manganese mixed salt solution is subjected to a first spray pyrolysis to obtain a core. The core is then mixed with a coating solution and subjected to a second spray pyrolysis to obtain the coating ternary precursor based on spray pyrolysis.

[0008] The nickel-cobalt-manganese mixed salt solution includes a first additive, which includes a polyol substance;

[0009] The coating solution includes a second additive, which comprises a two-dimensional material.

[0010] The preparation method described in this invention is a spray pyrolysis process based on two pyrolysis steps. This process enables the efficient and controllable construction of a coating layer on the surface of precursor particles in a transient high-temperature field. By atomizing and spraying the precursor solution and performing segmented heat treatment, the nucleation, growth, and crystallization of the coated precursor are completed within a sub-second to second time. This results in a uniform and dense modification layer on the surface of the high-nickel ternary material. This coating structure can effectively suppress the initiation and propagation of microcracks in the single-crystal cathode material caused by lattice volume changes and electrolyte side reactions during long-term cycling of lithium-ion batteries. It significantly improves the structural integrity and interface stability of the electrode material. Furthermore, this preparation process can greatly shorten the preparation cycle and avoid batch inconsistencies and cost increases caused by multi-step separation, washing, and redispersion. At the same time, it can improve the battery capacity and cycle performance.

[0011] Furthermore, in order to make the elemental distribution in the core more uniform and improve the morphology, the present invention adds polyols to the nickel-cobalt-manganese mixed salt solution used in the first spray pyrolysis to increase the solution viscosity, slow down the evaporation rate, prolong the micro-reaction time, promote the uniform distribution of nickel-cobalt-manganese and control the particle morphology. At the same time, a two-dimensional material is added to the coating solution used in the second spray pyrolysis. The two-dimensional material is adsorbed onto the surface of the core particles in the slurry through π-π interactions and hydrogen bonding to form a layered protective film. The coating ions are electrostatically adsorbed between the layers of the two-dimensional material and transformed into a two-dimensional continuous coating layer after spray pyrolysis, thereby obtaining a uniform and dense coating layer.

[0012] Preferably, the polyols include ethylene glycol and / or glycerol.

[0013] Preferably, the content of the first additive in the nickel-cobalt-manganese mixed salt solution is 1wt%-3wt%, for example, it can be 1wt%, 1.5wt%, 2wt%, 2.5wt% or 3wt%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0014] The content of the first additive in the nickel-cobalt-manganese mixed salt solution of the present invention will affect the uniformity of element distribution in the core. If the content of the first additive is too low, the defects in the material will increase and the uniformity of element distribution will decrease. If the content of the first additive is too high, the morphology of the particles will be irregular and the consistency and density will decrease.

[0015] Preferably, the two-dimensional material comprises graphene oxide and / or carbon nitride.

[0016] Preferably, the content of the second additive in the coating solution is 1wt%-3wt%, for example, it can be 1wt%, 1.5wt%, 2wt%, 2.5wt% or 3wt%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0017] The amount of the second additive added to the coating solution described in this invention will affect the coating effect. If the amount of the second additive added is too small, the coating effect will decrease. However, if the amount of the second additive added is too large, the interfacial resistance will increase and the capacity of the material will decrease.

[0018] Preferably, in the nickel-cobalt-manganese mixed salt solution, the molar ratio of nickel ions, cobalt ions, and manganese ions is x:y:(1-xy), where x is 0.85-0.95, for example, 0.85, 0.87, 0.89, 0.91, 0.93, or 0.95, and y is 0.02-0.05, for example, 0.02, 0.03, 0.04, or 0.05, but is not limited to the listed values; other unlisted values ​​within the range are also applicable.

[0019] Preferably, the total metal ion concentration in the nickel-cobalt-manganese mixed salt solution is 50 g / L-150 g / L, for example, it can be 50 g / L, 70 g / L, 90 g / L, 110 g / L, 130 g / L or 150 g / L, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0020] Preferably, the coating solution includes any one or a combination of at least two of manganese ions, aluminum ions, and cerium ions.

[0021] Preferably, the molar ratio of the core to the total metal ions in the coating solution is 1:(0.1-0.3), for example, it can be 1:0.1, 1:0.15, 1:0.2, 1:0.25 or 1:0.3, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0022] Preferably, the total metal ion concentration in the coating solution is 10 g / L-30 g / L, for example, it can be 10 g / L, 15 g / L, 20 g / L, 25 g / L or 30 g / L, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0023] Preferably, the temperature of the first spray pyrolysis is 700℃-900℃, for example, it can be 700℃, 750℃, 800℃, 850℃ or 900℃, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0024] The temperature of the first spray pyrolysis in this invention will affect the pyrolysis effect. If the temperature of the first spray pyrolysis is too low, a ternary oxide powder with good crystallinity will not be obtained. If the temperature of the first spray pyrolysis is too high, the powder will be over-sintered and severely agglomerated.

[0025] Preferably, the time for the first spray pyrolysis is 15s-20s, for example, it can be 15s, 16s, 17s, 18s, 19s or 20s, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0026] Preferably, the temperature of the second spray pyrolysis is 700℃-800℃, for example, it can be 700℃, 725℃, 750℃, 775℃ or 800℃, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0027] If the temperature of the second spray pyrolysis in this invention is too low, a product with complete manganese coating on the surface will not be obtained; if the temperature of the second spray pyrolysis in this invention is too high, the crystallinity of the manganese coating layer on the surface will be too high.

[0028] Preferably, the second spray pyrolysis time is 20s-25s, for example, it can be 20s, 21s, 22s, 23s, 24s or 25s, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0029] In a second aspect, the present invention provides a spray-pyrolysis-based coated ternary precursor, which is prepared by the preparation method described in the first aspect.

[0030] Thirdly, the present invention provides a battery in which the precursor for preparing the positive electrode material of the battery includes a coated ternary precursor based on spray pyrolysis as described in the second aspect.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] High-nickel single-crystal cathode materials are prone to microcracks during long-cycle charge-discharge processes, which expose the active surface and exacerbate side reactions with the electrolyte, leading to decreased interfacial stability and performance degradation. Constructing a uniform inert or ion-conducting coating layer through surface modification can effectively suppress crack propagation and reduce interfacial side reactions, making it a key strategy for improving the structural integrity and electrochemical stability of this material. Compared to the traditional co-precipitation method with its multi-step reaction and lengthy (typically requiring tens of hours) preparation process, the secondary spray pyrolysis process provided by this invention integrates precursor synthesis and surface coating into a continuous spray system, significantly shortening the preparation cycle to the hour level. It also avoids the batch inconsistencies and cost increases caused by multi-step separation, washing, and redispersion. This technology exhibits outstanding process efficiency and scalability, meeting the demands of the power battery industry for rapidly increasing the production of highly consistent and stable cathode materials. Detailed Implementation

[0033] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.

[0034] Example 1

[0035] This embodiment provides a method for preparing a coated ternary precursor based on spray pyrolysis, the method comprising the following steps:

[0036] A nickel-cobalt-manganese mixed salt solution is prepared, comprising nickel, cobalt, and manganese ions with a total metal ion concentration of 100 g / L and a molar ratio of 0.85:0.05:0.10, and further comprising 2 wt% glycerol; a coating solution is prepared, comprising manganese and aluminum ions with a total metal ion concentration of 20 g / L and a molar ratio of 1:1, and further comprising 2 wt% graphene oxide;

[0037] The nickel-cobalt-manganese mixed salt solution is atomized by a spray gun and passed through a furnace. It is then subjected to a first heating decomposition at 800°C for 18 seconds to obtain the core. The core is then mixed with a coating solution to obtain a mixed slurry, wherein the molar ratio of the total metal ions in the core to the coating solution is 1:0.2. The mixed slurry is atomized by a spray gun and passed through a furnace again. It is then subjected to a second heating decomposition at 760°C for 22 seconds to obtain the coated ternary precursor based on spray pyrolysis.

[0038] Example 2

[0039] This embodiment provides a method for preparing a coated ternary precursor based on spray pyrolysis, the method comprising the following steps:

[0040] A nickel-cobalt-manganese mixed salt solution is prepared, comprising nickel, cobalt, and manganese ions with a total metal ion concentration of 150 g / L and a molar ratio of 0.90:0.02:0.08, and further comprising 1 wt% ethylene glycol; a coating solution is prepared, comprising manganese and aluminum ions with a total metal ion concentration of 10 g / L and a molar ratio of 1:2, and further comprising 3 wt% carbon nitride;

[0041] The nickel-cobalt-manganese mixed salt solution is atomized by a spray gun and passed through a furnace, where it is heated and decomposed at 900°C for 15 seconds to obtain the core. The core is then mixed with a coating solution to obtain a mixed slurry, wherein the molar ratio of the total metal ions in the core to the coating solution is 1:0.3. The mixed slurry is atomized by a spray gun and passed through a furnace again, where it is heated and decomposed at 700°C for 25 seconds to obtain the coated ternary precursor based on spray pyrolysis.

[0042] Example 3

[0043] This embodiment provides a method for preparing a coated ternary precursor based on spray pyrolysis, the method comprising the following steps:

[0044] A nickel-cobalt-manganese mixed salt solution is prepared, comprising nickel, cobalt, and manganese ions with a total metal ion concentration of 50 g / L and a molar ratio of 0.95:0.02:0.03, and further comprising 3 wt% glycerol; a coating solution is prepared, comprising manganese and aluminum ions with a total metal ion concentration of 30 g / L and a molar ratio of 2:1, and further comprising 1 wt% graphene oxide;

[0045] The nickel-cobalt-manganese mixed salt solution is atomized by a spray gun and passed through a furnace, where it is heated and decomposed at 700°C for 20 seconds to obtain the core. The core is then mixed with a coating solution to obtain a mixed slurry, wherein the molar ratio of the total metal ions in the core to the coating solution is 1:0.1. The mixed slurry is atomized by a spray gun and passed through a furnace again, where it is heated and decomposed at 800°C for 20 seconds to obtain the coated ternary precursor based on spray pyrolysis.

[0046] Example 4

[0047] This embodiment provides a method for preparing a coated ternary precursor based on spray pyrolysis. The preparation method is the same as in Example 1, except that the content of glycerol in the nickel-cobalt-manganese mixed salt solution is 0.5 wt%.

[0048] Example 5

[0049] This embodiment provides a method for preparing a coated ternary precursor based on spray pyrolysis. The preparation method is the same as in Example 1, except that the content of glycerol in the nickel-cobalt-manganese mixed salt solution is 6 wt%.

[0050] Example 6

[0051] This embodiment provides a method for preparing a coated ternary precursor based on spray pyrolysis. The preparation method is the same as in Example 1, except that a first heating decomposition is performed at 600°C.

[0052] Example 7

[0053] This embodiment provides a method for preparing a coated ternary precursor based on spray pyrolysis. The preparation method is the same as in Example 1, except that a first heating decomposition is performed at 1000°C.

[0054] Example 8

[0055] This embodiment provides a method for preparing a coated ternary precursor based on spray pyrolysis. The preparation method is the same as in Example 1, except that the content of graphene oxide in the coating solution is 0.5 wt%.

[0056] Example 9

[0057] This embodiment provides a method for preparing a coated ternary precursor based on spray pyrolysis. The preparation method is the same as in Example 1, except that the content of graphene oxide in the coating solution is 6 wt%.

[0058] Example 10

[0059] This embodiment provides a method for preparing a coated ternary precursor based on spray pyrolysis. The preparation method is the same as in Example 1, except that a second heating decomposition is performed at 600°C.

[0060] Example 11

[0061] This embodiment provides a method for preparing a coated ternary precursor based on spray pyrolysis. The preparation method is the same as in Example 1, except that a second heating decomposition is performed at 900°C.

[0062] Comparative Example 1

[0063] This comparative example provides a method for preparing a coated ternary precursor based on spray pyrolysis. The preparation method is the same as in Example 1, except that the nickel-cobalt-manganese mixed salt solution does not contain glycerol.

[0064] Comparative Example 2

[0065] This comparative example provides a method for preparing a coated ternary precursor based on spray pyrolysis. The preparation method is the same as in Example 1, except that the coating solution does not contain graphene oxide.

[0066] Comparative Example 3

[0067] This comparative example provides a method for preparing a coated ternary precursor based on spray pyrolysis. The preparation method is the same as in Example 1, except that the coating solution is replaced with an equal volume of deionized water.

[0068] The precursors obtained in the above examples and comparative examples were mixed with LiOH and then sintered at 750°C for 12 hours to obtain positive electrode materials. The sintered positive electrode materials were then mixed with conductive agents and binders (such as PVDF) in N-methylpyrrolidone solvent at a certain mass ratio to prepare a positive electrode slurry. The positive electrode slurry was uniformly coated on an aluminum foil current collector, dried, rolled, and then cut or punched into positive electrode sheets of the required size for later use. Using a lithium metal sheet as the negative electrode, a polypropylene microporous membrane as the separator, and a 1 mol / L lithium hexafluorophosphate (LiPF6) carbonate mixed solvent solution as the electrolyte, the prepared positive electrode sheets were assembled into a coin cell in a glove box filled with an inert atmosphere.

[0069] Electrochemical performance tests were conducted on the coin cells under the following conditions: charge-discharge tests were performed at room temperature (25°C). The test voltage range was 2.8~4.5V, and constant current charge-discharge cycles were performed at different current densities (e.g., 0.1C, 0.2C, 1C, etc.).

[0070] The test results are shown in Table 1 below:

[0071] Table 1

[0072]

[0073] As can be seen from Table 1 above:

[0074] As shown in Example 1 and Comparative Example 1, the addition of the first additive to the nickel-cobalt-manganese mixed salt solution of the present invention can improve the uniformity of element distribution, improve morphology, and enhance the performance of the material. As shown in Example 1 and Comparative Example 2, the addition of the second additive to the coating solution of the present invention can improve the coating effect. As shown in Example 1 and Comparative Example 3, the spray pyrolysis coating method of the present invention can obtain a uniform and dense coating layer, improving battery performance. As shown in Example 1 and Examples 4-5, the amount of the first additive added in the present invention affects its effect. As shown in Example 1 and Examples 6-7, and as shown in Example 1 and Examples 10-11, the temperatures of the first and second spray pyrolysis in the present invention both affect the performance of the material, thereby affecting the performance of the battery. As shown in Example 1 and Examples 8-9, the amount of the second additive added in the present invention affects the coating effect, thereby affecting the performance of the battery.

[0075] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the scope of protection and disclosure of the present invention.

Claims

1. A method for preparing a coated ternary precursor based on spray pyrolysis, characterized in that, The preparation method includes the following steps: A nickel-cobalt-manganese mixed salt solution is subjected to a first spray pyrolysis to obtain a core. The core is then mixed with a coating solution and subjected to a second spray pyrolysis to obtain the coating ternary precursor based on spray pyrolysis. The nickel-cobalt-manganese mixed salt solution includes a first additive, which includes a polyol substance; The coating solution includes a second additive, which comprises a two-dimensional material.

2. The preparation method according to claim 1, characterized in that, The polyols include ethylene glycol and / or glycerol; Preferably, the content of the first additive in the nickel-cobalt-manganese mixed salt solution is 1wt%-3wt%.

3. The preparation method according to claim 1 or 2, characterized in that, The two-dimensional material includes graphene oxide and / or carbon nitride; Preferably, the content of the second additive in the coating solution is 1wt%-3wt%.

4. The preparation method according to claim 1 or 2, characterized in that, In the nickel-cobalt-manganese mixed salt solution, the molar ratio of nickel ions, cobalt ions, and manganese ions is x:y:(1-xy), where x is 0.85-0.95 and y is 0.02-0.

05. Preferably, the total metal ion concentration in the nickel-cobalt-manganese mixed salt solution is 50 g / L-150 g / L.

5. The preparation method according to claim 1 or 2, characterized in that, The coating solution includes any one or a combination of at least two of manganese ions, aluminum ions, and cerium ions; Preferably, the molar ratio of the core to the total metal ions in the coating solution is 1:(0.1-0.3).

6. The preparation method according to claim 1 or 2, characterized in that, The total metal ion concentration in the coating solution is 10 g / L-30 g / L.

7. The preparation method according to claim 1 or 2, characterized in that, The temperature of the first spray pyrolysis is 700℃-900℃; Preferably, the time for the first spray pyrolysis is 15s-20s.

8. The preparation method according to claim 1 or 2, characterized in that, The temperature of the second spray pyrolysis is 700℃-800℃; Preferably, the second spray pyrolysis time is 20s-25s.

9. A coated ternary precursor based on spray pyrolysis, characterized in that, The spray pyrolysis-based coated ternary precursor is prepared by the preparation method described in any one of claims 1-8.

10. A battery, characterized in that, The precursor for preparing the positive electrode material in the battery includes the coated ternary precursor based on spray pyrolysis as described in claim 9.

Citation Information

Patent Citations

  • Coated precursor oxide as well as preparation method and application thereof

    CN118791054A